Penyesuaian Diri, Dukungan Sosial, dan Gaya Belajar Visual terhadap Stres Akademik Siswa di Masa Pandemi - Riva Nadia Putri; Nurul Hidayah; Mujidin (Fakultas Psikologi, Universitas Putra Indonesia YPTK Padang, 2021)
This study aims to test empirically the effect of self adjustment, social support, visual learning style on academic stress in seventh grade students of SMP Negeri X Yogyakarta. This research method is a quantitative method with a Likert scale model as a data collection tool. The subjects of this study were seventh grade students of SMP X Yogyakarta. The sampling technique was carried out by cluster random sampling technique. Data analysis of this research is multiple regression analysis technique with the help of SPSS 21 program. The results of data analysis showed: (1) there was a very significant influence between self-adjustment, social support, visual learning style on academic stress as indicated by F reg = 107.076 with p value = 0.000 (p <0.01). (2) there is an effect of adjustment to academic stress which is indicated by the value of t = -13,349 with a value of p = 0.000 (p <0.01). (3) there is no significant effect between social support and academic stress as indicated by the value of t = -1.726 with a value of p = 0.086 (p>0.01). (4) There is no significant effect between visual learning style and academic stress which can be seen from the value of t = 1.944 with a value of p = 0.054 (p>0.01). The conclusion of this research is that there is an effect of self adjustment, social support, visual learning style on academic stress.